A collection of visual trigonometric proofs - Veronica Bitonti , Francesco Laudano (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
We present a collection of new visual proofs of the principal trigonometric relationships, that allow covering trigonometry in continuity with the topics of Euclidean geometry, without having to give up on demonstrations. With this work we want also to highlight the importance of geometric reasoning in the didactic field, as its formative value seems even greater, in particular with distance learning. As a matter of fact, in this condition it becomes unrealistic to keep young students’ attention focused on long sequences of formal passages, whereas it would be more effective to stimulate them to think about geometric figures